Philosophy and the role of cooperatives in the development of social capital. Case study: rural women’s microcredit cooperatives in Iran - Alireza Ranjbari; Mohammad Sadegh Ebrahimi; Gholamhossein Khedri (Boletín de la Asociación Internacional de Derecho Cooperativo)
The empowerment of people in the society by synergizing the components of social capital (awareness, cohesion, trust and participation) causes transformation in that society. The aim of this study was to investigate the Philosophy and the role of cooperatives in the development of social capital. The statistical population of this study were women members of microcredit funds in Marvdasht Township in Iran. According to the database information, they include 2000 and from this number, 200 statistical samples were selected based on Cochran’s sampling formula and completely randomly. The main research tool was a questionnaire. The validity of the questionnaire was confirmed using the opinions of university professors and experts, and its reliability was also confirmed using Cronbach’s alpha coefficient higher than 80%. The results of the research showed that the index of social capital and components of awareness, trust, participation, cohesion and networks were weak in women. The results of the study showed that there is a positive and significant relationship between the empowerment of fund members and social capital (awareness, cohesion, trust, participation and networking). Among the factors affecting social capital, risk-taking with a beta coefficient of 0.637 has been the most important factor affecting the development of social capital of women members of credit funds. The results of the research emphasize that people’s participation in cooperative activities will create a social base for people and then social identity and cohesion for them, which will ultimately lead to the empowerment of rural women.